HYPOCRISY AMONG THE UPPER CLASS IN OSCAR WILDE'S LADYWINDERMERE'S FAN (1892): A SOCIOLOGICAL APPROACH - MAYASARI, FITRIA (2011)
The objective of the study is to analyze the play based on its structural analysis and based on sociological analysis. This study is a qualitative study. The object of the study is Oscar Wilde's Lady Windermere's Fan played for the first time in 1892 in London. The data sources are divided into two, namely primary data source and secondary data source. The primary is the play itself and the secondary data source is other sources relating to the analysis such as the author biography, books of literary theory and also sociological books. The method of data collection is library research. The technique of data analysis is descriptive analysis. The conclusions of the study are as follows. First, based on the structural analysis, it is evident that in this play, Oscar Wilde suggests the idea that the upper class tends to be hypocritical. In order to illustrate the idea, Wilde creates such characters as Mr. Dumby and Duchess of Berwick who get difficulty in accepting things as they are. Second, based on the sociological analysis Wilde through Lady Windermere's Fan play reflects the condition in that time especially the condition of the upper class society and also as the document of the history in the end of the nineteenth century. Third, In Lady Windermere's Fan, Wilde wants to criticize the upper class that tends to be hypocritical.